Paradigms of international human rights law - Fellmeth, Aaron Xavier (New York, NY : Oxford University Press, 2016)
'Paradigms of International Human Rights Law' explores the legal, ethical, and other policy consequences of three core structural features of international human rights law: the focus on individual rights instead of duties; the division of rights into substantive and nondiscrimination categories; and the use of positive and negative right paradigms.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 15, 2016).
Keywords: Human rights; International law; Law